1965
DOI: 10.1039/tf9656102246
|View full text |Cite
|
Sign up to set email alerts
|

Heats of immersion of alpha and gamma alumina

Abstract: The heats of immersion of a-AI203 and y-Al2O3 in water, benzene, five n-butyl derivatives, and an epoxy resin in benzene, have been determined at 25°C. Values for the heats of immersion of alumina on substrate aluminium in the same liquids have been recalculated, and they show that the immersional properties of this solid approximate to those of y-Al2O3. Immersion of all three solids in water, a-Al2O3 in n-butyraldehyde and y-Al2O3 in n-butyl alcohol, give rise to high heats, which are indicative of a contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1968
1968
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Recently, an immiscible phase method developed by Albertson20 has also been used to obtain contact angles on cell layers. 4,21 Present results show that it is difficult to eliminate surface tension reduction for a water drop contacting a biological surface and the relation ylv < ylv0 will hold for most cases. Consequently, the simultaneous determination of both contact angle and surface tension under these experimental conditions is a necessary extension to current practice.…”
Section: Resultsmentioning
confidence: 82%
“…Recently, an immiscible phase method developed by Albertson20 has also been used to obtain contact angles on cell layers. 4,21 Present results show that it is difficult to eliminate surface tension reduction for a water drop contacting a biological surface and the relation ylv < ylv0 will hold for most cases. Consequently, the simultaneous determination of both contact angle and surface tension under these experimental conditions is a necessary extension to current practice.…”
Section: Resultsmentioning
confidence: 82%
“…The trend observed for the order of the perpendicular orientation of PPP (eq 2) also seems to be accounted for on the basis of surface energy or strength of interaction between PPP and the substrate. It has been reported that the heat of wetting H w of carbon, aluminum, and copper in benzene, which corresponds to the monomer unit of PPP, increases in the following order: 31 The large H w value of Cu seems to originate from π-coordination of benzene to the transition metal, and a number of π-benzene complexes of various transition metals including Cu and Ag have been isolated. 32 Thus, the higher order of the perpendicular orientation of PPP on the carbon substrate seems to be attributable to the weaker interaction of the PPP molecule with carbon.…”
Section: Resultsmentioning
confidence: 99%
“…To increase the amount of hydroxyl groups [26], and to allow for a larger reactant reservoir in ∼ 5 nm small pores, the fibers were coated with γ-alumina atop of the AKP-30 smoothing layer. The use of γ-alumina intermediate layers has been studied elaborately for, for instance, the fabrication of high performance inorganic gas separation membranes [27].…”
Section: Fiber Fabrication and Coatingmentioning
confidence: 99%